Conformation‐Controlled Molecular Sieving Effects for Membrane‐Based Propylene/Propane Separation. Issue 14 (15th February 2019) - Liu, Yang; Chen, Zhijie; Liu, Gongping; Belmabkhout, Youssef; Adil, Karim; Eddaoudi, Mohamed; Koros, William
Abstract: Membrane‐based separation is poised to reduce the operation cost of propylene/propane separation; however, identifying a suitable molecular sieve for membrane development is still an ongoing challenge. Here, the successful identification and use of a metal–organic framework (MOF) material as fillers, namely, the Zr‐ fum ‐fcu ‐MOF possessing an optimal contracted triangular pore‐aperture driving the efficient diffusive separation of propylene from propane in mixed‐matrix membranes are reported. It is demonstrated that the fabricated hybrid membranes display a high propylene/propane separation performance, far beyond the current trade‐off limit of polymer membranes with excellent properties under industrial conditions. Most importantly, the mechanism behind the exceptional high propylene/propane selectivity is delineated by exploring theoretically the efficiency of sieving of different conformers of propane through the hypothesized triangular rigid pore‐aperture of Zr‐ fum ‐fcu ‐MOF. Abstract : The traditional understanding of the molecular sieving effect is refined by considering the CC single bond rotation in C3 H6 and C3 H8 molecules. Zr‐ fum ‐fcu ‐MOF with trefoil‐like pore‐aperture is therefore rationally selected as efficient C3 H6 /C3 H8 fillers in mixed matrix membranes (MMMs). The fabricated MMMs shows excellent C3 H6 /C3 H8 separation performance, far beyond the trade‐off of polymer membranes.